O computador como ferramenta de aprendizagem frente os alunos do 5º ano do Ensino Fundamental I na Escola Estadual Mário David Andreazza - FREITAS, Dayane Maciel de (Instituto Federal do Amapá, 2021)
The present article intends to include the technologies of the use of the computer, as a learning tool, in order to allow the teachers to make the computer lab of the schools a necessary extension of their practices developed in the classroom, instilling limits and rules to the student as to its use. Inserting in their daily planning activities to be developed by their students. Therefore, the aim of this work is to encourage education professionals to reflect on the ethical use of the computer and make them aware of the importance that this tool has and can be an ally in their daily work.